2020
DOI: 10.1021/acsaem.0c00903
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effects of Nitrogen Atoms of Supports on Pt–Ni Rhombic Dodecahedral Nanoframes for Oxygen Reduction

Abstract: Pt-based nanostructures immobilized on carbon supports have been widely used as electrocatalysts. Their catalytic activity can be improved by support modification including nitrogen doping and coating with nitrogen-containing polymers, where nitrogen atoms possibly interact with surface Pt atoms at a catalyst/support interface. To understand electronic effects of nitrogen-doped and polymer-coated carbon supports on the catalytic activity of Pt-based nanostructured catalysts, we prepared Pt 3 Ni nanoframes (NFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Interestingly, the comparison between LSVs of (Cu,Fe)–N–CNT and Pt/C undergoing the negative sweep revealed that these E 1/2 values for the ORR were the almost same (Figure S7). Generally, E 1/2 values of LSVs for PGM-based ORR electrocatalysts including Pt/C highly depend on the potential sweep direction, and their LSVs undergoing the negative sweep tend to show more negative E 1/2 than those undergoing the positive sweep since the surface of PGM catalysts can be covered with metal oxide or hydroxide species (M–O­(H)) under oxidative conditions. , This is the reason why representative LSVs of Pt/C are usually shown in the positive-going sweep (Figure ). However, in practice, ORR catalysts with higher catalytic activity undergoing the negative-going sweep should be developed because PEFCs should provide the peak power for fuel cell vehicles during acceleration.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the comparison between LSVs of (Cu,Fe)–N–CNT and Pt/C undergoing the negative sweep revealed that these E 1/2 values for the ORR were the almost same (Figure S7). Generally, E 1/2 values of LSVs for PGM-based ORR electrocatalysts including Pt/C highly depend on the potential sweep direction, and their LSVs undergoing the negative sweep tend to show more negative E 1/2 than those undergoing the positive sweep since the surface of PGM catalysts can be covered with metal oxide or hydroxide species (M–O­(H)) under oxidative conditions. , This is the reason why representative LSVs of Pt/C are usually shown in the positive-going sweep (Figure ). However, in practice, ORR catalysts with higher catalytic activity undergoing the negative-going sweep should be developed because PEFCs should provide the peak power for fuel cell vehicles during acceleration.…”
Section: Resultsmentioning
confidence: 99%
“…155,164,165 In addition to oxidative polymerization, an easy-handling process involving a simple mixing of the carbon support with an organic entity containing solution followed by a thorough rinsing step has been applied for overcoating with PyPBI, PBI and PVP. 78,[159][160][161][162][166][167][168] Moreover, by utilizing the amide reaction between the -COOH groups of carbon black and the -NH 2 groups of amine-terminated poly(N-isopropylacrylamide) (PNIPAM), Jung et al 169 demonstrated the covalent functionalization of the carbon support with polymers for efficient anchoring of metal species. Of note, since the polymer overlayer can strongly interact with the surface of carbon materials, the subsequent metal deposition and coordinating interactions with functional groups (such as N-containing groups) will be feasible.…”
Section: Modification Of the Carbon Support By Surface Overcoatingmentioning
confidence: 99%
“…As a result, PtCo/C-PNIPAM displayed higher ORR activity and degradation resistance, in comparison with PtCo/C without PNIPAM functionalization. However, it was recently demonstrated by Kato et al 167 that the PBI overlayer on the carbon support could not impose an effect on the electronic structure of PtNi nanoframes immobilized but, instead, tended to stabilize Pt-(OH) ad species under the ORR conditions for activity improvement. Indeed, they found the electronic effect from the corresponding N-doped carbon-supported PtNi catalyst.…”
mentioning
confidence: 99%
“…[40][41][42] The surface of carbon materials evenly and strongly attached to polybenzimidazole through p-p interactions, indicating that the high-dispersibility Pt NPs were immobilized by nitrogen atoms to achieve better catalytic performance for ORR. [43][44][45] Pt NPs have also been prepared by NaBH 4 and ethylene glycol methods. Pt NPs in Pt/MnO 2 -carbon nanobers were prepared using NaBH 4 , and the resultant catalysts exhibit excellent electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%